2009
DOI: 10.1037/a0013703
|View full text |Cite
|
Sign up to set email alerts
|

The perception of temporal order along the mental number line.

Abstract: R. Sekuler, P. Tynan, and E. Levinson (1973) found that when 2 characters are presented side-by-side with a short onset asynchrony, subjectively they often appear in a "first-left, then-right" order. The authors of this article conducted 6 experiments in which observers judged the temporal order (TOJs) in which 2 digits were presented. They found a consistent TOJ benefit (larger d;) when the numerically smaller digit was presented first, even though this semantic information was irrelevant to the task and unre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 68 publications
6
29
0
Order By: Relevance
“…On the face of it, our findings could be seen as being more compatible with an interaction at an early representational rather than at a late decision stage (e.g., Risko et al, 2013;Schwarz & Heinze, 1998;Szűcs & Soltész, 2007); however, it should be stressed that SDT models per se are mute with respect to chronometric aspects. More generally, our findings clearly fit in with, and further extend, previous results from a variety of perceptual tasks (e.g., Casarotti, Michielin, Zorzi, & Umiltà, 2007;Corbett, Oriet, & Rensink, 2006;Fischer, Castel, Dodd, & Pratt, 2003;Godwin, Hout, & Menneer, 2014;Nieder, 2005;Schwarz & Eiselt, 2009 suggesting that symbolic numerical meaning is extracted at an early processing stage from visual displays containing digits, and under favorable (i.e., congruent) conditions, may enhance perceptual sensitivity, even in basic psychophysical tasks involving judgments about physical size.…”
Section: >5) and Physical Size (S Vs L)supporting
confidence: 77%
See 1 more Smart Citation
“…On the face of it, our findings could be seen as being more compatible with an interaction at an early representational rather than at a late decision stage (e.g., Risko et al, 2013;Schwarz & Heinze, 1998;Szűcs & Soltész, 2007); however, it should be stressed that SDT models per se are mute with respect to chronometric aspects. More generally, our findings clearly fit in with, and further extend, previous results from a variety of perceptual tasks (e.g., Casarotti, Michielin, Zorzi, & Umiltà, 2007;Corbett, Oriet, & Rensink, 2006;Fischer, Castel, Dodd, & Pratt, 2003;Godwin, Hout, & Menneer, 2014;Nieder, 2005;Schwarz & Eiselt, 2009 suggesting that symbolic numerical meaning is extracted at an early processing stage from visual displays containing digits, and under favorable (i.e., congruent) conditions, may enhance perceptual sensitivity, even in basic psychophysical tasks involving judgments about physical size.…”
Section: >5) and Physical Size (S Vs L)supporting
confidence: 77%
“…This claim is consistent with the general theory of magnitude (ATOM) positing that there is a common cortical metric underlying several quantity-related attributes, such as space, time, and number (e.g., Bonato, Zorzi, & Umiltà, 2012;Cohen Kadosh, Lammertyn, & Izard, 2008;Eiselt & Nieder, 2013;Henik, Leibovich, Naparstek, Diesendruck, & Rubinsten, 2012;Leon & Shadlen, 2003;Schwarz & Eiselt, 2009;Walsh, 2003;Winter, Marghetis, & Matlock, 2015). For example, in their coalescence diffusion model Schwarz and Ischebeck (2003) proposed that information from taskirrelevant attributes (e.g., numerical magnitude, and physical font size S vs. L) often cannot be completely ignored.…”
Section: >5) and Physical Size (S Vs L)supporting
confidence: 62%
“…Previous studies have shown that, upon presentation of two tones with different durations, responses were more accurate when the first tone was shorter or the second tone was longer (Conson et al, 2008) as if a preference for increasing temporal intervals would exist (see Lindemann et al, 2008, for a similar finding in the numerical domain). Nicholls et al (2011) questioned the results of Schwarz and Eiselt (2009) and suggested that some associations between dimensions such as size, duration, and number can be in fact due to response biases rather than to the presence of common cognitive processes. Sometimes effects apparently due to a modulation upon perception are in fact due to response biases and/or task-specific methodological biases, rather than to the true nature of number-time interactions (Grassi and Bonato, 2012).…”
Section: Interactions Between Numbers and Timementioning
confidence: 99%
“…This category encompasses studies that reported number-time interactions in the form of an association of small magnitudes with "before" responses and of large magnitudes with "after" responses (Müller and Schwarz, 2008;Schwarz and Eiselt, 2009). Schwarz and Eiselt (2009) used a temporal order judgement task in which the stimuli that were presented on the screen with variable asynchrony were pairs of numbers (one on the left and one on the right of fixation).…”
Section: Interactions Between Numbers and Timementioning
confidence: 99%
“…For temporal duration judgements, Oliveri et al (2008) demonstrated that durations in which a relatively large digit (e.g., 9) was presented were judged to last longer than those in which a smaller digit (e.g., 1) was presented. A link between number and time has also been observed for temporal order judgements by Schwarz and Eiselt (2009). In their first experiment, digits were presented to the left and right of a central fixation point.…”
mentioning
confidence: 99%